Conclusions - Weijing Deng (A+BE: Architecture and the Built Environment)
This thesis examined the housing opportunities of young Chinese adults (roughly 25 to 40 years of age) in post-reform China. The aim was to understand how these opportunities are related to the institutional changes that took place during the reform. In that respect, ample attention was paid to the complex and mutual connections between the welfare system, the housing system (particularly home ownership), and the kinship system. One chapter was devoted to a policy review and three to the empirical investigation. With this thesis, I hoped to help fill two gaps in the literature: